Al-Amin Living Lab and Industrial Park Waste Management Program - Rahmadhani Fitri; Faurantia Faurlana Sigit; Benny Iskandar; Andini Rahmadani (International Journal of Mechanical, Industrial and Control Systems Engineering, 2024)
The population growth that aligns with the increasing diverse needs will lead to an increase in waste or residues, both from consumption processes and the results of activities carried out, in the form of garbage. The purpose of this study is to understand the planning of the waste management system at Al-Amin Living Lab and Industrial Park. The research material is the site location in Sampe Cita Village, Kutalimbaru District, Deli Serdang Regency, considering and taking into account the existing waste management system. Littering will affect the activities of the surrounding community, which can ultimately lead to disease. The data used in the study of the management system involves several data collection techniques, namely, field observation and document analysis, direct observation in the field to observe waste management practices, such as collection, sorting, transportation, and disposal. Based on the results of the study, it is explained that the general activities of waste management planning at Al-Amin Living Lab and Industrial Park include containment, collection, transfer, and transportation of waste to the landfill. In terms of waste management planning at Al-Amin Living Lab and Industrial Park, it will consider the needs of people, the amount of waste generated, containment, and the TPST of Al-Amin Living Lab and Industrial Park area, as well as effective waste management.